2011
DOI: 10.1093/molbev/msr237
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Mutation Accumulation in Asexual Timema Stick Insects

Abstract: Sexual reproduction is extremely widespread in spite of its presumed costs relative to asexual reproduction, indicating that it must provide significant advantages. One postulated benefit of sex and recombination is that they facilitate the purging of mildly deleterious mutations, which would accumulate in asexual lineages and contribute to their short evolutionary life span. To test this prediction, we estimated the accumulation rate of coding (nonsynonymous) mutations, which are expected to be deleterious, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 54 publications
5
58
4
Order By: Relevance
“…Therefore, these interesting findings in vertebrates seem to imply that a similar mechanism might operate in the triploid vertebrates including Carassius auratus gibelio. In invertebrates, the mixture use of unisexual and sexual reproduction was also observed in some social insects (Wenseleers and Van Oystaeyen, 2011) and in some freshwater snails (Neiman et al, 2010), and deleterious mutation accumulation was revealed to play important role in limiting the long-term persistence of unisexual lineages (Henry et al, 2012). Through tracking the fate of modifier alleles that alter the frequency of sex and recombination, Keightley and Otto (2006) revealed that as there were a great number of deleterious mutations, a certain percentage of sexual reproduction could exert a positive effect to remove deleterious mutations.…”
Section: Evolutionary Implication Of Unisexual and Sexual Reproductiomentioning
confidence: 98%
“…Therefore, these interesting findings in vertebrates seem to imply that a similar mechanism might operate in the triploid vertebrates including Carassius auratus gibelio. In invertebrates, the mixture use of unisexual and sexual reproduction was also observed in some social insects (Wenseleers and Van Oystaeyen, 2011) and in some freshwater snails (Neiman et al, 2010), and deleterious mutation accumulation was revealed to play important role in limiting the long-term persistence of unisexual lineages (Henry et al, 2012). Through tracking the fate of modifier alleles that alter the frequency of sex and recombination, Keightley and Otto (2006) revealed that as there were a great number of deleterious mutations, a certain percentage of sexual reproduction could exert a positive effect to remove deleterious mutations.…”
Section: Evolutionary Implication Of Unisexual and Sexual Reproductiomentioning
confidence: 98%
“…These predictions appear to be largely upheld Lynch et al 2016). In asexual species, selection will favor an intermediate mutation rate, which generates sufficient advantageous, while not generating too many deleterious mutations (Paland and Lynch 2006; Henry et al 2012). However, relatively few species appear to be truly asexual.…”
Section: Introductionmentioning
confidence: 99%
“…One possible intrinsic factor is the accumulation of deleterious mutations (Lynch et al, 1999). Henry et al (2011) and Barraclough et al (2007) showed that deleterious mutations are more prevalent in asexually reproducing populations.…”
Section: Relevance Of Abnormal Femalesmentioning
confidence: 99%